Stilbenoid compounds inhibit NF-κB-mediated inflammatory responses in the Drosophila intestine - Aalto, Anna L.; Saadabadi, Atefeh; Lindholm, Fanny; Kietz, Christa; Himmelroos, Emmy; Marimuthu, Parthiban; Salo-Ahen, Outi M. H.; Eklund, Patrik; Meinander, Annika (Frontiers in Immunology, 2023)
Stilbenoid compounds have been described to have anti-inflammatory properties in animal models in vivo, and have been shown to inhibit Ca 2+ -influx through the transient receptor potential ankyrin 1 (TrpA1). To study how stilbenoid compounds affect inflammatory signaling in vivo, we have utilized the fruit fly, Drosophila melanogaster, as a model system. To induce intestinal inflammation in the fly, we have fed flies with the intestinal irritant dextran sodium sulphate (DSS). We found that DSS induces severe changes in the bacteriome of the Drosophila intestine, and that this dysbiosis causes activation of the NF-κB transcription factor Relish. We have taken advantage of the DSSmodel to study the anti-inflammatory properties of the stilbenoid compounds pinosylvin (PS) and pinosylvin monomethyl ether (PSMME). With the help of in vivo approaches, we have identified PS and PSMME to be transient receptor ankyrin 1 (TrpA1)-dependent antagonists of NF-κB-mediated intestinal immune responses in Drosophila. We have also computationally predicted the putative antagonist binding sites of these compounds at Drosophila TrpA1. Taken together, we show that the stilbenoids PS and PSMME have anti-inflammatory properties in vivo in the intestine and can be used to alleviate chemically induced intestinal inflammation in Drosophila.